CLINICAL PERFORMANCE OF ORAL LIQUID CHILDREN SICKLY ARVI - L.F. Kaskova; O.S. Pavlenkova (Український стоматологічний альманах)
The high prevalence and intensity of dental caries among children of our country - one of the most urgent problems of modern pediatric dentistry. Particular attention should be paid to preventing caries in various somatic diseases, including acute respiratory viral infections.